Possibilities of using technical regulations of customs union 012/2011 in Ukraine - Тіхенко, Валентин Миколайович; Меженков, Костянтин Володимирович; Антоненко, Тетяна Сергіївна (Eastern-European Journal of Enterprise Technologies, 2014)
In view of recent events that occur in relations between the two countries, Ukraine and Russia, the issue of maintaining successful economic positions of Ukrainian manufacturers of explosion-proof equipment in Russian-Ukrainian relations is becoming very important. The paper deals with current problems in the field of technical regulation, standardization, conformity assessment of explosion-proof equipment and removal of technical barriers to mutual trade in this equipment with the neighboring CIS countries. As a result of the study, a comparative analysis of existing technical regulations of Ukraine (TR 898) and Russia (TR CU 012/2011) was conducted, the main contradictions of these documents were highlighted and a reasonable assessment of the effects of using TR CU 012/2011 on alternative or non-alternative basis by Ukrainian business entities was given. The results are of practical importance and can be used for further in-depth study of the impact of technical barriers on business entities of explosion-proof equipment in Ukraine when using technical regulations of the Customs Union. The analysis and conclusions, presented in this paper are of interest of government and non-government agencies and organizations that deal with the above problem.